2019
DOI: 10.3847/2041-8213/ab3042
|View full text |Cite|
|
Sign up to set email alerts
|

Record-breaking Coronal Magnetic Field in Solar Active Region 12673

Abstract: At the Sun, the strongest magnetic fields are routinely detected at dark sunspots. The magnitude of the field is typically about 3000 G, with only a few exceptions that reported the magnetic field in excess of 5000 G. Given that the magnetic field decreases with height in the solar atmosphere, no coronal magnetic field above ∼2000 G was ever reported. Here, we present imaging microwave observations of anomalously strong magnetic field of about 4000 G at the base of the corona in solar active region NOAA 12673 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 24 publications
2
38
0
2
Order By: Relevance
“…Several significant coronal mass ejections (CMEs) were launched during its disk passage (Redmon et al 2018). Furthermore, this "monster" active region exhibited highly unusual characteristics and extreme behavior including the fastest flux emergence ever recorded (Sun & Norton 2017), the strongest transverse, (Wang et al 2018) and coronal magnetic fields (Anfinogentov et al 2019). Figure 1 includes an animation of these data for 2017 September 1-7.…”
Section: Magnetic Field Evolution Of Ar 12673mentioning
confidence: 99%
“…Several significant coronal mass ejections (CMEs) were launched during its disk passage (Redmon et al 2018). Furthermore, this "monster" active region exhibited highly unusual characteristics and extreme behavior including the fastest flux emergence ever recorded (Sun & Norton 2017), the strongest transverse, (Wang et al 2018) and coronal magnetic fields (Anfinogentov et al 2019). Figure 1 includes an animation of these data for 2017 September 1-7.…”
Section: Magnetic Field Evolution Of Ar 12673mentioning
confidence: 99%
“…Radio spectral observations of type III bursts, spike structures associated with type IV bursts and zebra patterns could also provide estimates of the magnetic field in the coronal source regions of the radio emission [21][22][23]. In addition, when the emission mechanisms are known, microwave imaging at one or more frequencies could be used to produce maps of the coronal magnetic field strength in limited regions [24][25][26][27][28][29]. More recently, the phenomenon of magnetic-fieldinduced transition (MIT) [30] has caught the attention of the solar physics community, and theoretical and laboratory investigations have demonstrated the potential of MIT lines in measurements of the coronal magnetic field [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, this has not been observed before. Numerical simulation of the magnetic structure and gyroresonance emission of NOAA 12673 in [Anfinogentov et al, 2019] has shown that the NLS observed at 17 and 34 GHz corresponded to the unusually high magnetic field strength detected at the photospheric level.…”
Section: Active Region Noaa 12673mentioning
confidence: 96%